Creating A Stunting-Recovered Village Through A Local Food-Based Weaning Food Menu Demonstration for Human Development Cadres in North Bonde Village, Majene: Mewujudkan Desa Pulih Stunting Melalui Demonstrasi Menu MP-ASI Berbasis Pangan Lokal Pada Kader Pembangunan Manusia Desa Bonde Utara, Majene - Mayangsari, Riska; Syah, Justiyulfah; Chaerul Anwaer, Muh (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
North Bonde Village is one of the villages that is a stunting locus in Majene Regency. The high number of stunting is caused by the low use of local food by the community. The purpose of this service is to increase the knowledge and skills of KPM and the community in making local food -based MP ASI innovations, which are also an independent effort to reduce stunting numbers. Mitra in this service activity is KPM and mothers who have toddlers, as many as 40 participants. PKM activities are carried out in the form of education and cooked demonstrations. The implementation of activities is divided into 3 stages, namely the education preparation phase, the implementation stage of the activity and then the third stage of the evaluation of the implementation of the activity. The results of the pre-post test obtained related to knowledge about the practice of providing the right MP-ASI/snacks that is before being given education is identified that most participants answered wrong (55.8%), after education the results of post-test knowledge increased by 50%so that an increase in correct answers was 94.2%. Then the results of the cooking demonstration are assessed objectively by looking at the processed MP-ASI results, all participants (100%) are able to make processed MP-ASI that are demonstrated. Local Food -Based Cooking Education and Demo is proven to be effective in increasing the knowledge and skills of mothers of toddlers, so it is recommended to be replicated in other stunting locus areas as an independent effort to accelerate stunting decreases.